Differences in stock return, corporate value, and risk based on the SRI-KEHATI index status in Indonesia Stock Exchange - Kukuh Fertion (Universitas Hayam Wuruk Perbanas, 2015)
Recent studies are paid attention to see whether there is a difference among the factors related to stock in companies listed in stock exchange. Therefore, it is also salient to do the same research so that more evidence can be gathered. The purpose of this research is to find the differences in stock return, corporate value, and risk between the compa-nies listed on SRI-KEHATI Index and those, which are not listed in SRI-KEHATI Index. This research uses secondary data taken from public companies listed on Indo-nesia Stock Exchange (BEI). The population consists of the companies listed on SRI-KEHATI Index to be compared with the companies listed in Indonesia Stock Exchange (BEI) from 2010 to 2013. The purposive sampling method is used in this study accord-ing to the criteria of assessment. The quantitative method is used to analyze this study. The signaling theory is the basic theory of this research. The analysis technique is using independent sample t-test. The result indicates that there is no difference in stock return, corporate value, and risk between the companies listed and those which are not listed on SRI-KEHATI index.